THE INSPECTION AND THE CALIBRATION OF THE TACHOGRAPHS - MIOTLA, Piotr; Sylwester, GLOD (Trends in education, 2014)
A tachograph is a device which is used for registering:* the length of the covered distance,* the vehicle speed,* the periods of the operating time, the breaks and rest.We can divide tachographs into three types:* analogue tachograph for one driver,* analogue tachograph for two drivers,* digital tachograph for one or two drivers.We make the tachographs to control in order to adjust the correctness of the data record and the proper operation. The analogue tachographs wrote parameters down on the paper discs but the digital tachographs write them down on the cards which are bound to the particular drivers.
Keywords: didactics; tachograph; inspection of the tachograph; calibration of the tachograph.